Comprehensive plans as tools for enhancing coastal community resilience. Issue 11 (18th September 2020) - Cucuzza, Marina; Stoll, Joshua S.; Leslie, Heather M.
Abstract : Planning for change is critical to ensuring resilient coastal communities. In Maine, USA, the comprehensive planning process provides a platform for communities to articulate policies that address social, economic, and environmental issues. While comprehensive plans were initially required of municipalities to address urban sprawl over thirty years ago, a broad range of challenges face coastal communities today. Here, we report on an assessment of 30 comprehensive plans from coastal communities across the state. We analyzed the degree to which plans incorporate principles of social-ecological resilience. Our results reveal significant variability across comprehensive plans, with some communities addressing key indicators of resilience and others engaging with them in a limited way. By more explicitly incorporating principles of social-ecological resilience, the next-generation of comprehensive plans can be repurposed to serve as tools for communities to implement strategies that build adaptive capacity as they face unprecedented challenges and plan for a changing world.